Methods of analyzing the relationship between new business formation and regional development - Michael Fritsch (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
The paper reviews the approaches that have been followed for analyzing the effect of new business formation on regional development. It begins with an outline of how start-ups may affect regional development. In dealing with different ways of empirically assessing these effects, I particularly stress the importance of indirect effects and of accounting for sufficiently long time lags. Finally, I discuss the issue of causality as well as avenues for further research about this important topic.
Keywords: L26; M13; O1; O18; R11; 330; new business formation; employment; regional development